Przyczyny dysproporcji na rynku pracy - Onufer, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The main aim of the paper is to present reasons for disparities in the labour market in Poland. These disparities include differences in worker’s salaries and the potential to find employment. Comparing the situation in particular regions in Poland, we can show that conditions in the local labour markets differ in a significant way, most visibly in the form of regional unemployment rates. In the largest Polish urban centers unemployment has ceased to be a critical social and economic problem. However, in other parts of the country we can find regions where the rate of unemployment is as high as 30%. A number of factors which influence labour create a situation where eliminating the disproportions between local markets is not easy. Among these factors are: economic prosperity, population growth, and the social and occupational structure of people looking for jobs. In Poland, important factors which result in disproportional development of local labour markets include access to infrastructure that is necessary for entrepreneurs and the size of particular markets.
Keywords: rynek pracy; dysproporcje; Polska